6(x+2)-7=-3(x+3)

Simple and best practice solution for 6(x+2)-7=-3(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+2)-7=-3(x+3) equation:


Simplifying
6(x + 2) + -7 = -3(x + 3)

Reorder the terms:
6(2 + x) + -7 = -3(x + 3)
(2 * 6 + x * 6) + -7 = -3(x + 3)
(12 + 6x) + -7 = -3(x + 3)

Reorder the terms:
12 + -7 + 6x = -3(x + 3)

Combine like terms: 12 + -7 = 5
5 + 6x = -3(x + 3)

Reorder the terms:
5 + 6x = -3(3 + x)
5 + 6x = (3 * -3 + x * -3)
5 + 6x = (-9 + -3x)

Solving
5 + 6x = -9 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
5 + 6x + 3x = -9 + -3x + 3x

Combine like terms: 6x + 3x = 9x
5 + 9x = -9 + -3x + 3x

Combine like terms: -3x + 3x = 0
5 + 9x = -9 + 0
5 + 9x = -9

Add '-5' to each side of the equation.
5 + -5 + 9x = -9 + -5

Combine like terms: 5 + -5 = 0
0 + 9x = -9 + -5
9x = -9 + -5

Combine like terms: -9 + -5 = -14
9x = -14

Divide each side by '9'.
x = -1.555555556

Simplifying
x = -1.555555556

See similar equations:

| -18=4x+6 | | -4(2x-4)+8=-8x+24 | | 3x+23-13{16}= | | 4x-2-6x+8= | | -3(y-3)-(-9-8y)=4y | | -3=v*5-7 | | 0.3(2z+6)+19.4=0.7(2z-4) | | 6-2m=7m-6m | | -2(x+3)+5=3(x+4)+8 | | 8x-36x+5=0 | | -4*y+2=10 | | 4.2+x-1.4=75 | | x-5=10.5 | | -4*7+2=10 | | 2(3-2x)=-14 | | x+10x+25(43-2x)=373 | | 8x-y=42 | | Y^2-8X+2+X^2-2y=5 | | 9x^2-100y^4=0 | | -7(1+8v)=29 | | .75x+3=.25x+6 | | 5y+9-y=5+3y-3 | | 16t=80 | | 5x+3-2(x+1)=8x+3 | | (2x^2-5x)(12x^2-5x-2)=0 | | 2(3*x-8)=4(x+1) | | 4x-10+x+80=180 | | 32=-3f+5f | | 3n+12=3n+2 | | 3(x+3)=8x+5-5x+4 | | 8x-2y=42 | | 8x+6+7x+5=56 |

Equations solver categories